Cubic functions and Trigometric functions

Calculus Level 5

Let f ( x ) = x 3 + b x 2 + c x + d f(x) = x^3 + bx^2 + cx + d and g ( x ) = sin ( x ) + cos ( x ) g(x) = \sin(x) + \cos(x) , where f ( 0 ) = g ( 0 ) , f ( π 2 ) = g ( π 2 ) f(0) = g(0), f \left(\frac{\pi}{2}\right) = g\left(\frac{\pi}{2}\right) and 0 π 2 f ( x ) d x = 0 π 2 g ( x ) d x \displaystyle \int_{0}^{\frac{\pi}{2}} f(x) dx = \int_{0}^{\frac{\pi}{2}} g(x) dx .

If the area A A of the region bounded between by the curves g ( x ) g(x) and f ( x ) f(x) on [ π 4 , 0 ] \left[-\frac{\pi}{4},0\right] can be expressed as A = α + β λ π α α + ( λ π α α γ ) α A = \sqrt{\alpha} + \beta - \dfrac{\lambda\pi}{\alpha^{\alpha}} + (\dfrac{\lambda\pi^{\alpha}}{\alpha^{\gamma}})^{\alpha} , where α , β , λ \alpha,\beta,\lambda and γ \gamma are coprime positive integers, find α + β + λ + γ \alpha + \beta + \lambda + \gamma .


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
May 6, 2018

f ( 0 ) = g ( 0 ) = 1 d = 1 f(0) = g(0) = 1 \implies d = 1 and f ( π 2 ) = g ( π 2 ) = 1 2 π b + 4 c = π 2 f(\dfrac{\pi}{2}) = g(\dfrac{\pi}{2}) = 1 \implies \boxed{2\pi b + 4c = -\pi^2} and 0 π 2 g ( x ) d x \int_{0}^{\dfrac{\pi}{2}} g(x) dx = 0 π 2 sin ( x ) + cos ( x ) d x = sin ( x ) cos ( x ) 0 π 2 = 2 \int_{0}^{\dfrac{\pi}{2}} \sin(x) + \cos(x) dx = \sin(x) - \cos(x)|_{0}^{\dfrac{\pi}{2}} = 2 \implies

2 = 0 π 2 ( x 3 + b x 2 + c x + 1 ) d x = 1 4 x 4 + b 3 x 3 + c 2 x 2 + x 0 π 2 = π 4 2 6 + π 3 3 2 3 b + π 2 2 3 c + π 2 2 = \int_{0}^{\dfrac{\pi}{2}} (x^3 + bx^2 + cx + 1) dx = \dfrac{1}{4}x^4 + \dfrac{b}{3}x^3 + \dfrac{c}{2}x^2 + x|_{0}^{\dfrac{\pi}{2}} = \dfrac{\pi^4}{2^6} + \dfrac{\pi^3}{3 * 2^3}b + \dfrac{\pi^2}{2^3}c + \dfrac{\pi}{2} \implies

8 π 3 b + 24 π 2 c = 384 96 π 3 π 4 \boxed{8\pi^3b + 24\pi^2c = 384 - 96\pi - 3\pi^4}

2 π b + 4 c = π 2 \boxed{2\pi b + 4c = -\pi^2}

Solving the above system we obtain:

c = 384 96 π + π 4 8 π 2 c = \dfrac{384 - 96\pi + \pi^4}{8\pi^2} and b = 384 96 π + 3 π 4 4 π 3 b = -\dfrac{384 - 96\pi + 3\pi^4}{4\pi^3} \implies

π 4 0 f ( x ) d x = x 4 4 384 96 π + 3 π 4 3 4 π 3 x 3 + 384 96 π + π 4 2 8 π 2 x 2 + x π 4 0 = \int_{\dfrac{-\pi}{4}}^{0} f(x) dx = \dfrac{x^4}{4} - \dfrac{384 - 96\pi + 3\pi^4}{3 * 4\pi^3} x^3 + \dfrac{384 - 96\pi + \pi^4}{2 * 8\pi^2} x^2 +x|_{\dfrac{-\pi}{4}}^{0} = 27 π 4 2304 π + 6144 3072 -\dfrac{27\pi^4 - 2304\pi + 6144}{3072}

π 4 0 g ( x ) d x = π 4 0 sin ( x ) + cos ( x ) d x = sin ( x ) cos ( x ) π 4 0 = 2 1 \int_{\dfrac{-\pi}{4}}^{0} g(x) dx = \int_{\dfrac{-\pi}{4}}^{0} \sin(x) + \cos(x) dx = \sin(x) - \cos(x)|_{\dfrac{-\pi}{4}}^{0} = \sqrt{2} - 1

π 4 0 g ( x ) f ( x ) d x = 9 π 4 768 π + 1024 ( 2 + 1 ) 1024 = \implies \int_{\dfrac{-\pi}{4}}^{0} g(x) - f(x) dx = \dfrac{9\pi^4 - 768\pi + 1024(\sqrt{2} + 1)}{1024} =

2 + 1 3 π 4 + 9 π 4 1024 = 2 + 1 3 π 2 2 + ( 3 π 2 2 5 ) 2 = α + β λ π α α + ( λ π α α γ ) α α + β + λ + γ = 11 \sqrt{2} + 1 - \dfrac{3\pi}{4} + \dfrac{9\pi^4}{1024} = \sqrt{2} + 1 - \dfrac{3\pi}{2^2} + (\dfrac{3\pi^2}{2^5})^2 =\sqrt{\alpha} + \beta - \dfrac{\lambda\pi}{\alpha^{\alpha}} + (\dfrac{\lambda\pi^{\alpha}}{\alpha^{\gamma}})^{\alpha} \implies \alpha + \beta + \lambda + \gamma = \boxed{11} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...